Uso del beneficio económico del sector informal en Colombia en el 2016 (2017)
In the present investigation an informality analysis is carried out in Colombia from the Micro-establishments Survey conducted by the DANE for 2016, where the informal sector will be followed from a social class processes approach in which there is a presence of relations of capitalist and non-capitalist type proposed by Bhattacharya (2010) with the objective of calculating the economic benefit for informal enterprises; It is found that the informal sector is not homogeneous, but a duality is generated with the existence of these class processes. For this purpose, this benefit will be calculated by applying the study done by Bhattacharya in India with the micro-establishments survey.